Effectiveness of a PBL Curriculum in Preparing Electrical Engineering Students for Industry through SSDC - Satyanarayana, Salava V.; Madhavi, Pillalamarri (Journal of Engineering Education Transformations, 2025)
In recent days, conventional learning method moving towards the research methodology which approaches to develop industry-relevant curriculum in engineering education that involves Project-based learning. Research question is how SSDC enhances the student skills and how does it meet the demands of current industry? The effectiveness of the course can be improved by designing the course of study by make use of various learning’s through projects associated with academics. Researchers commended the need to develop competency models for each occupation or job, so as to define graduated students’ successful performance in a particular area of work through their technical knowledge to reach industry competencies. This represents the enhancing in traditional method research by implementing various Project-based learning strategies in inclusion to academics as per the industrial stipulation through Student Skill Development Center.